On the Power Dissipation of Embedded Memory Blocks Used to Implement Logic in Field-Programmable Gate Arrays. (11th February 2008) - Chin, Scott Y. L.; Lee, Clarence S. P.; Wilton, Steven J. E.
Abstract : We investigate the power and energy implications of using embedded FPGA memory blocks to implement logic. Previous studies have shown that this technique provides extremely dense implementations of some types of logic circuits, however, these previous studies did not evaluate the impact on power. In this paper, we measure the effects on power and energy as a function of three architectural parameters: the number of available memory blocks, the size of the memory blocks, and the flexibility of the memory blocks. We show that although embedded memories provide area efficient implementations of many circuits, this technique results in additional power consumption. We also show that blocks containing smaller-memory arrays are more power efficient than those containing large arrays, but for most array sizes, the memory blocks should be as flexible as possible. Finally, we show that by combining physical arrays into larger logical memories, and mapping logic in such a way that some physical arrays can be disabled on each access, can reduce the power consumption penalty. The results were obtained from place and routed circuits using standard experimental physical design tools and a detailed power model. Several results were also verified through current measurements on a 0.13 μ m CMOS FPGA.